Bridging the Digital Divide: Technological Advancements at MSU-Sulu (International Journal of Scientific Research and Management (IJSRM), 2025)
This study explores the role of technological advancements in transforming education and administration at Mindanao State University-Sulu (MSU-Sulu). Using a mixed-methods approach, the research analyzes the impact of digital learning platforms, ICT integration, digital tools for research, and global collaboration initiatives. Surveys, interviews, and focus group discussions revealed high satisfaction levels among stakeholders, with faculty rating digital tools and global collaboration opportunities most positively. However, challenges such as inconsistent infrastructure, limited training, and access disparities persist. Statistical analyses, including chi-square tests and regression models, underscored the critical need for targeted interventions to address these issues. The study concludes that investments in infrastructure, training, and partnerships are essential for maximizing the benefits of technological advancements. These findings offer valuable insights for administrators and educators aiming to enhance digital education and foster innovation in underserved regions.